Adapting to a Hard Situation: BIPA Teachers' Successful Strategies for Teaching Local Culture During the COVID-19 Pandemic - Laksono, Prayitno Tri; Ismiatun, Febti (REiLA : Journal of Research and Innovation in Language, 2023)
Teaching culture is now highly challanging for teachers of Bahasa Indonesia bagi Penutur Asing (henceforth: BIPA) or Indonesian Language for Foreign Speakers since it is conducted online during pandemic. Several strategies had been offered by numerous researchers and educators to be applied in BIPA teaching yet the results remained unsatisfactory. Thus, this study aimed to explore the strategy used in teaching local culture by BIPA teachers during online learning. Using descriptive qualitative design, researchers recruited thirty-three BIPA teachers who have experience teaching local culture for one year. They came from Indonesia, Malaysia, Switzerland, and Philipphines.Triangulation data were applied by distributing the questionnaires, conducting online classroom observation, and doing in-depth interviews. After all data were gathered, researchers followed the Miles and Huberman flow model for analysis. The results showed that BIPA teachers had limited time and interaction in the hard situation during the pandemic, therefore, teaching local culture by using online platform as one of the solutions since the students cannot interact directly with Indonesian speakers was worth to conduct. To support teaching local culture, BIPA teachers implemented three strategies, including watching cultural video shows, simplifying reading, and providing foreign students with more role-playing activities to engage with local cultures material. These strategies adequately assisted them in understanding the concept of Indonesian local culture and supported their communication ability with Indonesian speakers.